Ensaio clínico piloto na avaliação da resposta à terapia de fotobiomodulação e magnetoterapia em osteonecrose dos maxilares induzida pelo uso do alendronato de sódio - Rodriguez, André Carvalho (2020)
Bisphosphonates are drugs that act on bone metabolism, inhibiting calcium precipitation and bone resorption. Such drugs, when used for long periods in the con-trol of Osteoporosis, can cause adverse effects, such as Bisphosphonate Related Osteonecrosis of the Jaws (BRONJ), these being more frequent from 8% to 12%, when administered intravenously. However, it must be reported that complications, when they occur, are very severe and mutilating, affecting the quality of life of these patients. In order to study the action of Energy-Based Devices, such as Photobiomodu-lation therapy and Magnetotherapy, associated with the Gold Standart surgical treat-ment, we conducted a pilot, prospective clinical study in patients who made continu-ous use of Sodium Alendronate and developed BRONJ. Patients were divided into three groups, namely: Group I Placebo - Gold standard surgical treatment, Group II - surgical treatment + photobiomodulation and Group III - surgical treatment + Magnetotherapy. The evaluation carried out through biochemical tests and bone density (Hounsfield Unit - HU) by computed tomography (CT) of the face, in addition to the clinical examination evaluating the inflammatory process, tissue repair and analgesia The results in Group I demonstrated dehiscence in the suture after seven days, as well as greater inflammation, edema, erythema in the local mucosa, hema-toma on the face and pain. Groups II and III showed a reduction in phlogistic signs, with analgesia at all times, in addition to accelerated surgical wound healing, with primary closure. When comparing Groups 2 and 3, an increase in post-operative bone density was demonstrated in the Magnetotherapy Group. It is concluded that Photobiomodulation Therapy and Magnetotherapy demon-strated safety and efficacy in the treatment of BRONJ, by reducing phlogistic signs, faster healing and reduced postoperative morbidity and with lower cost for patients and the institution involved.